Sistem Pakar Diagnosis Hama Dan Penyakit Tanaman Jeruk Keprok Menggunakan Metode Dempster Shafer Berbasis Web - Buala, Adi Saldi (Jurusan Teknologi Informasi Universitas Semarang, 2024)
Soe Tangerines are a type of local orange from the Soe area and are one of the leading agricultural commodities in East Nusa Tenggara (NTT) Province. The fruit is round and small with an average diameter of between 5-7 cm. Oranges are an important need for Indonesian people. Although the harvest of these oranges has not yet reached its maximum potential, this is caused by several factors such as cultivation techniques, environmental conditions, as well as pest and disease attacks. These three factors can cause a decrease in productivity and even crop failure. Therefore, an expert system was designed using the Dempster Shafer method. This method aims to detect pests and diseases based on the symptoms that appear on Tangerine plants and provide solutions to overcome these problems. The goal is to reduce the risk of pest and disease attacks on plants. The test results used 50 case data from the TTS Regency Agriculture and Plantation Service. The system test results from 50 data produced 42 case data that were in accordance with the expert diagnosis, 6 data that were in accordance with the expert diagnosis but below the threshold of 80% and 8 data that were not appropriate. Testing system accuracy by comparing system and expert diagnosis results obtained accuracy results of 84%.